Real-World Treatment Efficacy of Ribociclib or Palbociclib Plus Fulvestrant in Hormone Receptor-Positive/HER2-Negative Metastatic Breast Cancer: Turkish Oncology Group (TOG) Study - Kahraman, Seda; Erul, Enes; Gumusay, Ozge; Guven, Deniz Can; Aksoy, Sercan; Basaran, Gul; Sendur, Mehmet Ali Nahit (Cig Media Group, Lp, 2025)
We conducted a multicenter, retrospective cohort study that included 522 patients with HR+/HER2-MBC treated with ribociclib or palbociclib in combination with fulvestrant. Although the three CDK4/6 inhibitors did not seem to differ significantly from each other in terms of effectiveness in a real-world context, they may vary depending primarily on the specific characteristics of the patient population being treated. Background: Real-world (RW) data provide valuable information about the effectiveness and safety of treatment modalities in the general population that is not limited by selection criteria in clinical studies. The aim of this study was to evaluate the effectiveness of palbociclib or ribociclib plus fulvestrant in hormone receptor-positive and human epidermal factor 2-negative metastatic breast cancer (HR + /HER2-MBC). Materials and methods: We conducted a multicenter, retrospective cohort study that included 522 patients with HR + /HER2-MBC treated with ribociclib or palbociclib in combination with fulvestrant. Results: Median real-world progression-free survival (mPFS) was 12.9 months (95% CI, 11.16-14.65) for the entire cohort, and no statistically significant difference was present between the palbociclib and ribociclib groups ( P = .70). Real-world median overall survival (mOS) was estimated to be 43.3 months (95% CI, 20-66.6) for the palbociclib group and 48.5 months (95% CI, NA-NA) for the ribociclib group and similar between the 2 groups ( P = .56). When evaluated for the entire group, there was a significant difference in mPFS between patients with primary and secondary endocrine resistance (8.6 and 13.5 months, P = .002), and this difference was more pronounced in the palbociclib arm (6.6 and 14.4 months, P = .006) than in the ribociclib arm (11.6 and 13.3 months, P = .064). Conclusion: Although the 3 CDK4/6 inhibitors did not seem to differ significantly from each other in terms of effectiveness in a real-world context, they may vary depending primarily on the specific characteristics of the patient population being treated.
Keywords: CDK 4/6 inhibitors; Fulvestrant; HR-positive; Metastatic breast cancer; Real-world data